Respuesta :

Answer:

u = -2

Step-by-step explanation:

Here is how to solve the equation,

[tex]7 - 6u = 5u + 29\\[/tex]

What I did first was isolate the variable by adding to both sides.

7 - 6u = 5u + 29

  + 6u   +6u      

7 = 11u + 29

Our new equation now needs to be simplified by subtracting from both sides, like so...

 7 = 11u + 29

-29          -29  

-22 = 11u

Time to divide and solve for the variable u.

[tex]\frac{-22}{11}[/tex] and [tex]\frac{11u}{11}[/tex]

That leaves us with, -2 = u

Hope this helps and have a great day!